ROLE OF PRINT MEDIA IN SUSTAINABLE DEVELOPMENT GOAL OF TRIBALS (Trinity Journal of Management, IT & Media (TJMITM), 2025)
This research explores the vital role of print media in advancing the sustainable development objectives for tribal communities. It examines the significant factors through which print media contributes to the progress and empowerment of indigenous populations. The findings highlight that print media serves as a powerful tool for promoting the social and political rights of tribal communities. It provides crucial information to indigenous individuals, enabling them to access essential knowledge and resources. By raising awareness about their rights, print media strengthens the judicial and social standing of tribal communities and garners support for their struggles among allied communities. Furthermore, print media plays a pivotal role in preserving and nurturing the culture, traditions, and heritage of tribal communities. It serves as a medium for safeguarding and promoting indigenous languages, customs, and cultural practices, which might otherwise fade away over time. The publications in print media amplify the voices of tribal communities, fostering cultural heritage for future generations. Additionally, print media acts as an important tool in empowering tribal communities and promoting community development. It provides a platform for tribal individuals to engage in discussions, share their experiences, and encourage mutual cooperation. Through the dissemination of community news, print media strengthens the bonds within tribal societies, fostering collective action for their development. In conclusion, this research underscores the critical role of print media in advancing sustainable development objectives for tribal communities. It highlights its contribution to the promotion of social and political rights, the preservation of cultural heritage, and the empowerment of indigenous populations. By recognizing and utilizing the potential of print media, stakeholders can effectively address the unique challenges faced by tribal communities and work towards their sustainable development.
Keywords: Print media; Indigenous communities; Sustainable develop ment; Empowerment; Information dissemination; Awareness; Culture preservation; Heritage, Advocacy; Education; Literacy; Community development; Data collection; Data classification; Research writing; Subject matter exploration; Social justice; Human rights; Cultural her itage; Community engagement